FIRST RECORDS OF PLINACHTUS IMITATOR (REUTER, 1891) (HETEROPTERA: COREIDAE: COREINAE) IN CROATIA, BOSNIA & HERZEGOVINA AND MONTENEGRO, WITH NOTES ON NEW HOST-PLANT RECORDS (Acta Entomologica Serbica, 2023)
The paper mentions the first findings of the bug Plinachtus imitator (Reuter, 1891) in Croatia, Bosnia and Herzegovina and Montenegro. All the findings were recorded in localities along the Adriatic coast, most often on Pistacia lentiscus, a plant that was already known as a host. Plinachtus imitator was recorded for the first time on a new host plant - Pistacia terebinthus in Trsteno, Croatia.